“La Rana y El Águila”: The Universidad Pedagógica y Tecnológica of Colombia Printing-Publishing House as a Reference for a Cultural Project, 1962-1986 - Numpaque Acosta, Andrea María (Historiografías, 2025)
This article is an examination of the influence generated by the publicly work containing university ideas and thoughts between the years 1962 and 1986, period of the existence of the publishing house “La Rana y El Águila”, as well as the factors and challenges that influenced its trajectory. The article shall explain the impact of its creation and demise on the academic and social community of the Universidad Pedagógica y Tecnológica de Colombia. It also addresses the technological changes in book production and reproduction and how these advances enabled the modernization of printing processes by favoring or altering traditional methods of print production.KeywordsPrinting-publishing, The Pedagogical and Technological University of Colombia, cultural history, “La Rana y El Águila”, reading, books